2018
DOI: 10.1016/j.bonr.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Bones in human CYP26B1 deficiency and rats with hypervitaminosis A phenocopy Vegfa overexpression

Abstract: Angulated femurs are present prenatally both in CYP26B1 deficient humans with a reduced capacity to degrade retinoic acid (RA, the active metabolite of vitamin A), and mice overexpressing vascular endothelial growth factor a (Vegfa). Since excessive ingestion of vitamin A is known to induce spontaneous fractures and as the Vegfa-induced femur angulation in mice appears to be caused by intrauterine fractures, we analyzed bones from a CYP26B1 deficient human and rats with hypervitaminosis A to further explore Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Because both an excess and lack of RA are detrimental for most tissues, regulation of its concentration by CYP26 enzymes needs to be appropriately controlled (56)(57)(58)(59)(60). In the seminiferous epithelium, the major CYP26 enzyme that hydrolyzes RA is CYP26B1 (18,32).…”
Section: Discussionmentioning
confidence: 99%
“…Because both an excess and lack of RA are detrimental for most tissues, regulation of its concentration by CYP26 enzymes needs to be appropriately controlled (56)(57)(58)(59)(60). In the seminiferous epithelium, the major CYP26 enzyme that hydrolyzes RA is CYP26B1 (18,32).…”
Section: Discussionmentioning
confidence: 99%
“…Complementary DNA (cDNA) was synthesized from 400 ng RNA using High Capacity cDNA Reverse www.nature.com/scientificreports www.nature.com/scientificreports/ rabbit against aa 273-301 (PA5-13494, ThermoFisher Scientific). The primary antibody for detection of OPN N-terminal (OPN-N) was a custom made polyclonal and raised in rabbit against aa 46-58 (OPN 4557 "Liam") recognizing aa 30-42 in mature OPN-a, OPN-b and iOPN 16,17 (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…(2008) showed that adding a large amount of VA to the diet could reduce the growth of broilers and increase the incidence of leg diseases. Excessive VA may lead to diseases such as spontaneous bone fracture, abnormal calcium and phosphorus deposition, and reduced bone strength in poultry ( Thomas et al., 2017 , 2018 ; Navarro-Valverde et al., 2018 ). The results of Manston (1966) showed that dietary supplementation with excessive VA reduced intestinal absorption of calcium and phosphorus, and thus reduced the content of serum calcium and phosphorus.…”
Section: Discussionmentioning
confidence: 99%